An investigation of factors that hinder and support the career progression of South African black female researchers within a research and development (R&D) environment - Zama, Nokuthula (Organisational Psychology, 2017)
The challenges women face in progressing to senior ranking positions are widely acknowledged and have been investigated in numerous studies, both in South Africa and abroad. The present study sought to contribute to this body of knowledge by identifying factors that hinder, as well as support specifically black South African female researchers in progressing to senior ranking positions within a Research and Development or scientific organisation. Research and Development (R&D) organisations within the Science, Engineering and Technology (SET) sector, as is the case in most South African organisations, have seen an increase in the employment of female researchers, particularly at lower ranking positions. However, there seem to be factors that continually hinder black South African female researchers from being appointed into senior ranks, despite clear growth and development strategies and processes, training and development opportunities and increasing organisational support that is meant to bring about greater gender equity at the senior levels. As such, it proved imperative to undertake this study not only to understand the factors that support or hinder the progress of black South African women researchers into senior ranking positions, but also to ensure that organisations develop responsive and supportive interventions that facilitate the advancement of this cohort of researchers. A quantitative approach to addressing the research question was utilised. Following a literature review to identify both individual and organisational/structural level factors that have been shown to either support or hinder the career success of woman, an online questionnaire was developed and distributed to all the female researchers (of all race groups, career levels and age groups) employed in a South African R&D organisation (n=104). Data was obtained from a convenient sample of them (n=41). It was noted though that at the time the data was collected there were no black South African females employed in the highest scientific/researcher rank of the organisation. Whilst the organisation seems to deploy resources equally to all its' employees, black South African women continue to be under represented at the top ranks in the organisation. Arguably, R&D organisations seem to perpetuate a masculine culture that makes it increasingly difficult for women in general to progress to higher ranking positions. It seems that the situation is being further exasperated by career advancement requirements that do not take into account the different roles that women typically need to fulfil at work and at home, nor that support work-life balance for them. It was apparent that the organisation did provide them with organisational and supervisory support and that they are found to be loyal to the organisation, however, women particularly black South African researchers still fail to progress to senior ranking positions in the organisation. Organisations struggle to achieve gender equity at the senior ranking positions, and hopefully the present study will provide some insight into factors that negatively affect the career advancement of female equity candidates in the organisation, while also providing insight into factors that have proven to facilitate this process. The outcomes of the present study would potentially lead to more structured frameworks and strategic female development programmes that ensure that black female South African researchers do indeed advance through the different ranks and achieve the highest ranks within the SET sector of the economy.